Uncovering the Solvation Structure of LiPF6‐Based Localized Saturated Electrolytes and Their Effect on LiNiO2‐Based Lithium‐Metal Batteries. Issue 36 (2nd August 2022) - Su, Laisuo; Zhao, Xunhua; Yi, Michael; Charalambous, Harry; Celio, Hugo; Liu, Yuanyue; Manthiram, Arumugam
Abstract: Electrolytes play a critical role in stabilizing highly reactive lithium‐metal anodes (LMAs) and high‐voltage cathodes for rechargeable lithium‐metal batteries (LMBs). Localized high concentration electrolytes (LHCEs) have achieved remarkable success in the context of LMBs. However, the state‐of‐the‐art LHCEs are based on LiFSI salt, which is prohibitively expensive. Here, the utility of low‐cost LiPF6 salt in localized saturated electrolytes (LSEs) with a series of solvents and diluents in LMBs with cobalt‐free LiNiO2 cathode is systematically explored. Experimental and theoretical analyses reveal that the unique solvation structure formed not only changes the distribution of solvents and anions but also alters the atom–atom distances within them, leading to different reduction and oxidation stabilities compared to low‐concentration electrolytes. In addition, LSEs help form LiF‐rich interphase layers on the LMA and LiNiO2 cathode, protecting the electrodes from degradation during cycling. Different LSEs also lead to differences in lithium plating morphology and impedance buildup during cycling, impacting the performance of LMBs. The solvent and diluent must be carefully selected for compatibility with a lithium salt when developing LHCEs and LSEs for LMBs. Abstract : Experimental and theoretical analyses reveal that the unique solvation structure formed in recently developed localized saturated electrolytes, not only changes the distribution of solvents and anions but also alters the atom–atom distances within them, leading to different reduction and oxidation stabilities compared to low‐concentration electrolytes.